Comparing the version 7 TRMM 3B43 monthly precipitation product with the TRMM 3B43 version 6/6A and Bureau of Meteorology datasets for Australia - Fleming, K.; Awange, Joseph (Bureau of Meterology, Australia, 2013)
Recently, Fleming et al. (2011) compared the Tropical Rainfall Measuring Mission (TRMM) 3B43 (version 6/6A) monthly product with the Australian Bureau of Meteorology (the Bureau) monthly gridded dataset for the period 1998 to 2010. They found that the two datasets generally show a strong spatial and temporal agreement with each other. Since then, a new release (version 7) of the TRMM 3B43 product has been made available. This note briefly compares the 3B43 versions 6/6A and 7 (3B43 v6/6A and v7, respectively) products to that provided by the Bureau within the context of the previous work of Fleming et al. (2011). It is found that 3B43 v7 displays an improved correlation with the Bureau dataset compared to 3B43 v6/6A, with a cross correlation for the entire time series of 0.970 for 3B43 v7 versus the Bureau, compared to 0.932 for 3B43 v6/6A versus the Bureau. This improvement is especially noticeable for several months (October 2006, January 2007, and October 2008) where 3B43 v6/6A showed a relatively poor correlation with the Bureau dataset. However, the generally decreased correlation and increased scatter between 3B43 v6/6A and the Bureau after 2004 was also noted with 3B43 v7, although not as strongly, with a cross correlation for the period 1998 to 2003 of 0.947 and 0.976 for 3B43 v6/6A and v7 versus the Bureau, respectively, while 0.919 and 0.965 are the corresponding values for the period between 2004 and 2010. The reason for the improvement in the results is beyond the scope of this work, but there were several modifications to the 3B43 processing, including the improved treatment of the rain gauge input. We therefore recommend that workers employing this TRMM product change to the latest version for their studies.